A simulation study for evaluating the performances of different types of house-hold radiant air conditioning systems. (25th February 2018) - Li, Zhao; Chen, Jianbo; Wang, Fei; Cui, Lingchuang; Qu, Minglu
Highlights: Three novel house-hold radiant air conditioning systems proposed. Simulated models regarding an apartment with different systems established. System energy performances simulated using experimentally validated models. Lower energy consumption obtained by VRF based system. Solution for THIC system in small-to-medium residential buildings provided. Abstract: As one potential solution of independent temperature and humidity control in small-to-medium scaled residential buildings, systems of outdoor air dehumidifier with radiant terminals attracted lots of researchers' interests. In this paper, three types of house-hold radiant air conditioning (A/C) systems, a conventional air source heat pump (ASHP) based, a high-temperature ASHP based and a novel variable refrigerant flow rate (VRF) based radiant A/C system, were proposed. Simulation models for three systems were established using Energy Plus. A prototype of the VRF based radiant A/C system was built and tested in an existed psychometric room. Testing results were compared with the simulated results showing that the average relative errors between them were less than 8%. Therefore, simulation studies were carried out to evaluate the energy performances of the three types of house-hold radiant A/C systems. Compared to the conventional ASHP based system, the high-temperature ASHP based system achieved 14.99% annual energy saving and the VRF based system 19.34%. Therefore, the VRF based system achieved the best energy efficiency, providing a promising solution for the house-hold radiant A/C system to realize the independent control of temperature and humidity in small-to-medium scaled residential buildings.